Surface modification improving the biological activity and osteogenic ability of 3D printing porous dental implants - Qin, Zugan; He, Yun; Gao, Jingjing; Dong, Zhihong; Long, Shuai; Cheng, Lijia; Shi, Zheng (Frontiers in Materials, 2023)
Objective: To explore the mechanical properties, biological activity, and osteogenic ability of 3D printed TC4 titanium (Ti) alloy dental implants treated with surface modification. Methods: Dental implants with 30% porosity were manufactured using selective laser melting (SLM) technology (group 3D), while traditional numerically-controlled machine tools (CNC) were used to manufacture implants without porosity (group SL). The implants were then surface modified through sandblasting and acid etching (groups 3DA1 and SLA1), and then alkali etching (groups 3DA2 and SLA2). The physicochemical properties of the implants were measured using a Vickers hardness instrument, scanning electron microscope (SEM), X-ray diffraction (XRD), energy dispersive spectrometer (EDS), and profilograph before and after surface modification. Next, the biocompatibility, bioactivity, and osteogenic ability of the implants were evaluated using apatite deposition experiments, alkaline phosphatase (ALP) activity, and semiquantitative analysis of extracellular matrix mineralization. Results: There were significant differences in morphology, geometric accuracy, mechanical properties, surface roughness, and hydrophilicity between groups 3D and SL. Furthermore, surface modification improved the physicochemical properties of the porous implants. Implants with sandblasting, acid etching, and alkali etching demonstrated better biocompatibility, bioactivity, and osteogenic ability than implants without surface modification in both groups 3D and SL. Additionally, the implants of groups 3D have higher bioactivity than that of groups SL. Conclusion: Surface modification and the macroporous structure of implants can improve their bioactivity and osteogenic ability, enhancing the application of Ti alloy dental implants.